Learning and teaching stage 4 clinical decision making: progression from novice to expert. Issue 9 (8th August 2022) - Crebbin, Wendy; Guest, Glenn; Beasley, Spencer; Tobin, Stephen; Duvivier, Robbert; Watters, David
Abstract: Background: This paper describes the development of learning from novice to expert in Stage 4: Clinical Decision Making (CDM) in surgery: Postoperative reflection and review. It also outlines some or the assessment and teaching approaches suitable to facilitate that transition in skill level. Methods: This paper is drawn from a much broader study of learning and teaching CDM, that used qualitative methodology based on Constructivist and Grounded Theory. Data was collected in individual interviews and focus groups. Using thematic analysis the data were analysed to identify key ideas. All participants worked in the Department of Surgery at one large regional hospital in Victoria. Results: For each stage there is a sequence of learning beginning from relying on external resources, gradually developing internal resources to guide and direct the learner's CDM. Those internal resources built through experience include multisensory and kinaesthetic memories that expand to facilitate the ability to cope with complexity. Discussion: Armed with the mind‐map and rubric table included in this paper it should be possible for any senior clinician or teacher to diagnose their trainees' progression in Stage 4 CDM. This will enable them to tailor their teaching to best match the capabilities of the trainee and to enable to be more effectively targeted. Conclusion: CDM can be taught and both trainees and senior clinicians can benefit from understanding the processes involved. Abstract : This article describes the development of learning from novice to expert in Stage 4 Clinical Decision making‐postoperative reflection and review. It also outlines some or the teaching approaches suitable to facilitate that transition.